Effect of spatial inlet velocity profiles on the vortex formation pattern in a dilated left ventricle - Chan, B.T.; Lim, Einly; Ong, C.W.; Abu Osman, Noor Azuan (Taylor & Francis, 2015)
Despite the advancement of cardiac imaging technologies, these have traditionally been limited to global geometrical measurements. Computational fluid dynamics (CFD) has emerged as a reliable tool that provides flow ?eld information and other variables essential for the assessment of the cardiac function. Extensive studies have shown that vortex formation and propagation during the filling phase acts as a promising indicator for the diagnosis of the cardiac health condition. Proper setting of the boundary conditions is crucial in a CFD study as they are important determinants, that affect the simulation results. In this article, the effect of different transmitral velocity profiles (parabolic and uniform profile) on the vortex formation patterns during diastole was studied in a ventricle with dilated cardiomyopathy (DCM). The resulting vortex evolution pattern using the uniform inlet velocity profile agreed with that reported in the literature, which revealed an increase in thrombus risk in a ventricle with DCM. However the application of a parabolic velocity profile at the inlet yields a deviated vortical flow pattern and overestimates the propagation velocity of the vortex ring towards the apex of the ventricle. This study highlighted that uniform inlet velocity profile should be applied in the study of the filling dynamics in a left ventricle because it produces results closer to that observed experimentally.